2017
DOI: 10.21831/jk.v1i1.10440
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Peaceful Mentality and Pesantren-Based School Rules

Abstract: This study was aimed at eliciting facts of peaceful conditions experienced by students in the environment of Pesantren-based schools, positively and negatively, and revealing the students’ mentality in the face of the school rules. The study was done in Madrasah Aliyah (Mualimin) Pesantren Persatuan Islam (PPI) 76 Tarogong, Garut. The study used the narrative method based on the data collected by questionnaires, interviews, observation, and literature study using interactive analyses. Findings show that the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
5
0
4
Order By: Relevance
“…Rules are also made so that students can respect the rules and learn to control themselves. This was also conveyed in a research which stated that the functions of school regulations include creating discipline, practicing responsibility, streamlining teaching and learning activities, strengthening the role of students, practicing honesty, independence, practice social skills, eliminate social jealousy, enhance a sense of community, and maintain comfort (Hidayat et al, 2017;Maskuri, 2018;Sobri et al, 2019). Therefore, the traditional mataluh turtle game can train children's discipline values.…”
Section: Discipline Valuementioning
confidence: 99%
“…Rules are also made so that students can respect the rules and learn to control themselves. This was also conveyed in a research which stated that the functions of school regulations include creating discipline, practicing responsibility, streamlining teaching and learning activities, strengthening the role of students, practicing honesty, independence, practice social skills, eliminate social jealousy, enhance a sense of community, and maintain comfort (Hidayat et al, 2017;Maskuri, 2018;Sobri et al, 2019). Therefore, the traditional mataluh turtle game can train children's discipline values.…”
Section: Discipline Valuementioning
confidence: 99%
“…Educators are obligated to provide educational services in a professional manner. Hidayat, Ilfiandra, and Kartadinata (2017) argued that educators are responsible not only for transferring knowledge, but also for demonstrating competence and professionalism. Lindfors, Pettersson, and Olofsson (2021) stated that future educators are charged with cultivating digital competence and playing an important role in both the labor market and the learning process of the 21st-century society.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, violence is one of the behaviors found in schools and classrooms in Indonesia. Both the teacher and the students carry out shouting, harsh expressions, even physical violence which then causes injury, injury and trauma (Akhmad & Kartadinata, 2016;Amalia & Ediati, 2017;Hidayat, Ilfiandra, & Kartadinata, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies related to classroom climate have always focused on their effects on learning outcomes and learning motivation, without delving deeper into why and how class climate is formed. Research conducted by Akhmad and Kartadinata (2016) and Hidayat et al (2017) revealed that the meaning of a peaceful classroom climate is a class climate in which it does not prioritize violence, mutual respect and encouragement between teachers and students. It is important for teachers to learn, understand, and carry out various ways to build a peaceful classroom climate, because a peaceful classroom climate can form a peaceful character as well which will then be able to optimize the various learning undertaken (Akhmad & Kartadinata, 2016;Hidayat et al, 2017;Navarro-Castro & Nario-Galace, 2010;Wuryandani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%